Manajemn Sistem Pergudangan/Warehouse Peralatan Laboratorium Teknik Mesin Universitas Riau Berbasis Komputerisasi - Arief, Dodi Sofyan; Iskandar, Anwar; Susilawati, Anita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The warehouse management is a system to manage a storage and handling of goods and material, which are stored and distributed in a right time, amount and the specification. The Laboratory of Mechanical Engineering, University of Riau is equipped with goods and material to support its activities. Hence, it is needed a system to manage the storage and handling of such equipments in optimal manner. Recently, the warehousingat the Laboratory of Mechanical Engineering, University of Riau has been used the manual system. Subsequent, there was not optimal to manage activities in the laboratory such as time consuming, mess of storage, difficulty in finding data equipments, etc. This research aim is to design and develop a warehouse management system of the Laboratory in Mechanical Engineering, Riau University. A method of 5S (Sort, Straighten, Shine, Standardize, Sustain) and the warehouse laboratory based information system were implemented in this research. Stages to construct the information system of warehouse management were: the design of database system, the menu structure, sub-systems and the display model of interface system (users interface). This systemwas developed using the programming language of the PHP (Hypertext Preprocessor) and MySQL as the database. The information system of laboratory based-computerization was useful for managing and monitoring the activities in Laboratory of Mechanical Engineering in form of incoming or outgoing the data of goods and material. While, the design of warehouse layout of facilities in laboratory of Mechanical Engineering, University of Riau used the 5S method, was produced clean and neatly arranged of the equipments and tools.Keywords : Warehouse management, 5S Method, PHP, MySQL, Information System.